Charming e-cigarette users with distorted science: a survey examining social media platform use, nicotine-related misinformation and attitudes towards the tobacco industry - Elexis C Kierstead; Barbara Schillo; Jodie Briggs; Nathan A Silver (BMJ Open)
Objective To examine the role of social media in promoting recall and belief of distorted science about nicotine and COVID-19 and whether recall and belief predict tobacco industry beliefs.Design Young adults aged 18–34 years (N=1225) were surveyed cross-sectionally via online Qualtrics panel. The survey assessed recall and belief in three claims about nicotine and COVID-19 and three about nicotine in general followed by assessments of industry beliefs and use of social media. Ordinal logistic regression with robust standard errors controlling for gender, race/ethnicity, education, current e-cigarette use and age was used to examine relationships between variables.Results Twitter use was associated with higher odds of recall (OR=1.21, 95% CI=1.01 to 1.44) and belief (OR=1.26, 95% CI=1.04 to 1.52) in COVID-19-specific distorted science. YouTube use was associated with higher odds of believing COVID-19-specific distorted science (OR=1.32, 95% CI=1.09 to 1.60). Reddit use was associated with lower odds of believing COVID-19-specific distorted science (OR=0.72, 95% CI=0.59 to 0.88). Recall (OR=1.26, 95% CI=1.07 to 1.47) and belief (OR=1.28, 95% CI=1.09 to 1.50) in distorted science about nicotine in general as well as belief in distorted science specific to COVID-19 (OR=1.61, 95% CI=1.34 to 1.95) were associated with more positive beliefs about the tobacco industry. Belief in distorted science about nicotine in general was also associated with more negative beliefs about the tobacco industry (OR=1.18, 95% CI=1.02 to 1.35).Conclusions Use of social media platforms may help to both spread and dispel distorted science about nicotine. Addressing distorted science about nicotine is important, as it appears to be associated with more favourable views of the tobacco industry which may erode public support for effective regulation.